Measuring thermal conductivity of frozen soil using fiber optic sensors - Zhu, Н.; Wu, В.; Cao, D. (Eurasian Journal of Applied Engineering and Technology (EJAET), 2021)
The thermal conductivity is crucial for determining heat transfer in frozen soil. However, it is a challenge to obtain accurate measurement values due to the instability of soil properties. Recently, the fiber optic sensing technologies has enabled accurate and distributed in-situ monitoring of a variety of geotechnical parameters. This paper aims to explore the feasibility of actively heated fiber Bragg grating (AH-FBG) method in measuring thermal conductivity of frozen soil. A series of laboratory experiments were performed on frozen soil samples at different initial temperatures from −16 to 5 ℃. The theoretical upper and lower limits of thermal conductivity were used to evaluate the AHFBG measurements. The thermal conductivity recorded by a heat transfer analyzer was used to identify the measurement accuracy. The experimental results that the AH-FBG method can accurately measure the thermal conductivity of frozen soil when the initial temperature is below −6 ℃, and the measurement error is within acceptable range of 0.8%. When the soil temperature is between −6 and 0 ℃, significant measurement errors were observed due to the disturbance of heating to the frozen soil.